Criança e cidade: territorialidades e possibilidades pedagógicas de professores de Educação Infantil de São Paulo - Bressane, Elaine Terrin (2023)
This research aims to study the conceptions regarding the presence of children in the city, as evoked by Early Childhood Education teachers in the municipality of São Paulo. The following questions guide the research: How do Early Childhood Education teachers understand children's appropriation of the city? Do their personal and professional experiences enable them to have contact and opportunities for socialization within urban spaces? How do these professionals use the city? Do their personal and professional experiences regarding spaces for social interaction reflect in the experiences they have with their students currently? Therefore, the overall objective of the research is to understand the factors that lead these adults, responsible for mediating and presenting the urban territory to children, to expand or restrict their access and right to the city. The specific objectives are: (1) to describe the profile of Early Childhood Education teachers in relation to their own use of the city, both regarding childhood experiences and adult/professional life experiences; (2) to verify the perception of these teachers regarding children's presence and relationship with the city and to identify the conceptions about the city and childhood that permeate their pedagogical practice; (3) to raise and analyze indications of teaching practices in the city-childhood relationship, concerning the planning and organization of learning activities; and (4) to identify the regulations and guidelines that support such practices. Data collection was carried out through an online electronic questionnaire distributed directly to Early Childhood Education educators in the municipality of São Paulo, without any ties to the analysis of the school unit, and the responses were organized and processed using Sphinx IQ2 software. Lefèbvre (2010) and Haesbaert (2007) support the analysis in light of the concept of territory and the right to the city, while Sarmento (2018) and Pinto provide the foundations regarding the sociology of childhood. Calliari (2016) addresses the specificities of growth, urban planning, and the relationship with public spaces in the municipality of São Paulo. The main results regarding the perception of the interviewed teachers regarding urban public space and its pedagogical possibilities were: (1) an uncertainty about what constitutes an "activity outside of school"; (2) the lack of consensus regarding the repertoire and pedagogical possibilities of using urban spaces, and sometimes even internal school spaces; and (3) the presence of specific spatial relationships within the CEUs (Educational Centers) caused by their unique architectural nature. The diffuse perception of urban public space and its pedagogical possibilities, as well as the lack of connection between certain specific activities such as walking and the use of public facilities as pedagogical activities, were the main results obtained. Thus, it is concluded that there is a gap between the territorialities experienced in practice and those conceptually advocated in legal frameworks, which may indicate an ideological process promoting intentional detachment from reality. Despite the achievements, these frameworks remain fragile tools against the power of Capital. Regarding perceptions of urban public space, they are formed within each person's life stories but also carry a series of perceptions that originate within a common sense influenced by society as a whole